A circulating microRNA panel enhances the diagnosis of cholangiocarcinoma - Aye Myat Mon; Kitti Intuyod; Sirinapha Klungsaeng; Apinya Jusakul; Arunnee Sangka; Vor Luvira; Chawalit Pairojkul; Tullayakorn Plengsuriyakarn; Kesara Na-Bangchang; Somchai Pinlaor; Porntip Pinlaor (PLoS ONE, 2025)
Background and aim Cholangiocarcinoma (CCA), a malignancy with a high incidence in regions endemic for the liver fluke Opisthorchis viverrini, is frequently characterized by alterations in the p53 tumor-suppressor gene, a process often modulated by microRNAs. Our study aimed to identify circulating miRNAs as potential diagnostic biomarkers for CCA. Methods We sequenced small RNAs to identify differentially expressed microRNAs (miRNAs) in two CCA cell lines (one p53-mutant, one p53-wildtype) relative to an immortalized cholangiocyte cell line. Candidate miRNAs exhibiting significant upregulation with a log2 fold change > 4.5 were selected for validation via RT-qPCR in serum samples from patients with CCA. The diagnostic utility of these serum miRNAs was subsequently evaluated using receiver operating characteristic (ROC) analysis to assess their ability to distinguish CCA from normal controls and hepatocellular carcinoma (HCC). This performance was assessed for the miRNAs as standalone markers and in combination with conventional tumor markers. Results Analysis of miRNA expression profiles identified seven upregulated candidates for validation. Among these, serum levels of miR-99a-5p, miR-516a-5p, and miR-526b-5p were significantly elevated in patients with CCA compared to both normal controls (all area under the curve, AUC > 0.79, p < 0.0001) and patients with HCC (all AUC > 0.80, p < 0.0001). A diagnostic panel combining these three miRNAs demonstrated high accuracy in distinguishing CCA from normal controls (AUC = 0.899) and from HCC (AUC = 0.937). The panel’s performance was further enhanced by incorporating conventional tumor markers, achieving an AUC of 0.928 when combined with CA19−9, and rising to 0.959 with the inclusion of both CA19−9 and CEA. Conclusions These findings indicate that a panel comprising miR-99a-5p, miR-516a-5p, and miR-526b-5p, alone or with established tumor markers, offers high accuracy as a minimally invasive diagnostic tool for CCA, and can effectively distinguish it from HCC.